2001
DOI: 10.1108/00368790110393910
|View full text |Cite
|
Sign up to set email alerts
|

Lubricant influence on flange wear in sharp railroad curves

Abstract: Since the middle of the 1970s, lubrication of the high rail flange has been used to reduce wear rates. Field tests have been taking place since 1997 to evaluate the differences in wear characteristics between mineral oil based grease and new environmentally adapted greases. The field tests have also investigated whether the addition of graphite contributed to reduced flange wear. The wear reducing effect of trackside lubrication as a function of distance from point of application of the grease was also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…Also the observation that the oxide layer increases the wear rate is in agreement with the Kalousek et al [16] observation that an rail surface martensitic layer is easily oxidised and helps accelerate wear. If one consider the low humidity level results, the trends of an increased wear rate when lowering the temperature is in agreement with the results of full scale test results of Waara [18]. Comparing our results with the work of Hardwick et al [17] we can see a difference that in our case an increased humidity did not change the wear rate at room temperature 20 °C.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Also the observation that the oxide layer increases the wear rate is in agreement with the Kalousek et al [16] observation that an rail surface martensitic layer is easily oxidised and helps accelerate wear. If one consider the low humidity level results, the trends of an increased wear rate when lowering the temperature is in agreement with the results of full scale test results of Waara [18]. Comparing our results with the work of Hardwick et al [17] we can see a difference that in our case an increased humidity did not change the wear rate at room temperature 20 °C.…”
Section: Discussionsupporting
confidence: 94%
“…During the testing, catastrophic wear occurred under dry conditions, but no transition to catastrophic wear occurred with water present in the contact. Waara [18] found that the field test concerning winter conditions gave higher wear rate than laboratory test in room temperature, both under dry and lubricated conditions. Another field test also showed that the precipitation has a significant effect on rail wear [19].…”
Section: Introductionmentioning
confidence: 97%
“…Other studies carried out in the field have shown improvements of a similar order of magnitude (Allen et al, 1985;Samuels et al 1987). Laboratory ; Clayton et al, 1989) and field (Waara, 2001;Olofsson and Nilsson, 2002) tests have all shown the wear-reducing benefits of lubrication at the wheel-rail contact. The Alvsjo test track (Olofsson and nilsson, 2002) is a good example: the worn rail area for the lubricated case was approximately one sixth of the worn area for the unlubricated case.…”
Section: Friction Modificationmentioning
confidence: 95%
“…Measurement of rail wear during inspection is normally made at three different positions as shown in Fig. 2: W1 is the vertical wear, W2 is the horizontal wear at a vertical distance h, and W3 is the wear measured at an angle ⍺ from the horizontal [3].…”
Section: Fig 1 Wheel Wear [1]mentioning
confidence: 99%